(untitled) (Bangladesh Heart Journal, 2021)
In surgical practice management of vascular injuries are challenging. Vascular injuries are well addressed in developed countries but there is scarcity of vascular surgeons in developing countries like us and a large number of victims fail to reach specialist in time with consequent loss of limbs or lives. To observe the pattern and outcome of management of vascular injury in a developing country this retrospective study was conducted at the department of vascular surgery, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh. All patients with vascular injury arrived alive were included in the study. Date in terms of age, sex, cause of injury, segment of vessel involved, associated injuries, time elapsed after injury, vascular procedures done and postoperative complications were taken from records of the department and were analyzed. Out of 2174 patients with vascular injury 11 patients died at resuscitation & 52 did not come back after referral to other hospitals for management of associated injuries. Most of the patients were young male & road traffic accidents was the most common cause (91.50%). Majority (53.60%) of the patients presented after 6 hours. Majority of the cases lower limb vessels were injured (64.05%). Among the associated injuries combine orthopedic & soft tissue injuries were most common (60.58%). Among the vascular procedures antilogous venous graft (42.39%) followed by end to end anastomosis (27.79%) were in majority of the cases. In case of extremity vascular injury limb amputation rate was 35.40%. This morbidity can be reduced by improvement of road safely measures, encouraging doctors to vascular surgery specialty and effective training of orthopedic & general surgeons in the management of extremity vascular injury till the availability of vascular surgeons for provision of vascular services in remote areas. Bangladesh Heart Journal 2021; 36(1) : 32-37